Some issues and problems in the governance of a metropolitan region - Oamar, Felipe V. (1977)
The creation of Metro Manila and the Metropolitan Manila Commission, which aims to establish a more responsive and effective government, raises some issues and problems concerned with the reorganization and government of metropolitan communities. These issues, based on observations made of several metropolitan areas, are: (a) possible undesirable effects of the "functional" and "integrational" reorganizational schemes, (b) proper definition of local and area-wide goods and services under a two-level government structure, (c) smaller, not larger, political units being more efficient organizations in the public sector, and (d) unequal service levels in different areas of the metropolis.
Keywords: Metropolitan government; Metropolitan Manila Commission; Public administration